UPAYA MEMINIMALISIR AKSI PRANK MELALUI PENANAMAN PENDIDIKAN MORAL PADA REMAJA - Khoerunisa, Nova; Nurus Sa’adah (UIN Sunan Kalijaga Yogyakarta, 2024)
Prank actions that are increasingly prevalent among teenagers are often without regard to the negative consequences, disrupting social order and reflecting moral decline. It is important to address this issue to protect the younger generation from harmful behavior and raise awareness of social responsibility. The purpose of this study is to discuss efforts to minimize prank actions through moral education in adolescents. Method. Applied in this research namely qualitative descriptive method whose sources are obtained from literature review. The results show that excessive pranks can trigger despicable behavior in adolescents, through the provision of moral education, adolescents will really want to be aware of good and bad things, and have a sense of compassion that can encourage adolescents to rethink their choice to do pranks. Moral education is effective in minimizing the negative impact of pranks by increasing adolescents' ethical awareness and social responsibility. Keywords: Prank, Moral Education, Teenager.